A hybrid intelligent GMPPT algorithm for partial shading PV system. (February 2019) - Mao, Mingxuan; Zhou, Lin; Yang, Zengrui; Zhang, Qianjin; Zheng, Chen; Xie, Bao; Wan, Yihao
Abstract: Maximum power extraction for PV systems under partial shading conditions (PSCs) relies on the optimal global maximum power point tracking (GMPPT) method used. This paper proposes a novel maximum power point tracking (MPPT) control method for PV system with reduced steady-state oscillation based on improved particle swarm optimization (PSO) algorithm and variable step perturb and observe (P&O) method. Firstly, the grouping idea of shuffled frog leaping algorithm (SFLA) is introduced in the basic PSO algorithm (PSO–SFLA), ensuring the differences among particles and the searching of global extremum. Furthermore, adaptive speed factor is introduced into the improved PSO to improve the convergence of the PSO–SFLA under PSCs. And then, the variable step P&O (VSP&O) method is used to track the maximum power point (MPP) accurately with the change of environment. Finally, the superiority of the proposed method over the conventional P&O method and the standard PSO method in terms of tracking speed and steady-state oscillations is highlighted by simulation results under fast variable PSCs. Highlights: Output characteristics of PV system under different PSCs. A hybrid intelligent GMPPT algorithm is proposed. Simulation experiments on the Simulink platform are conducted. The proposed algorithm reduces the steady-state oscillations.